Seismic performance of stiffened concrete-filled double skin steel tubes. (June 2020) - Wang, Zhi-Bin; Zhang, Jian-Bin; Li, Wei; Wu, Hong-Jun
Abstract: The concrete-filled double skin steel tubular (CFDST) members have been used in many engineering projects. The stiffened outer steel tube could be used to further enhance the structural performance and reduce the steel consumption, while the seismic behaviour of the stiffened member needs investigation. In this study, tests of 6 stiffened CFDST beam-columns were conducted under both constant axial load and cyclic lateral load. Main test parameters were the axial load level and the hollow section ratio. The load, deformation and strain of all specimens were recorded and analysed. The influence of parameters was discussed in terms of the lateral resistance, the ultimate displacement, the ductility and the energy dissipation ability. It showed that the stiffened specimens exhibited good energy dissipation capacity under the cyclic loading. A finite element (FE) model was developed to carry out the mechanism and parametric analysis. The longitudinal stiffeners could effectively reduce the local buckling of the tube wall. The ductility and energy dissipation capacity of stiffened CFDST members are generally higher than that of unstiffened ones. Finally, equations for predictions of the flexural stiffness and strength, as well as the hysteretic model of the load-deformation relationship were proposed for stiffened CFDST members. Highlights: We provide test data on the seismic behaviour of stiffened concrete-filled double skin steel tubular (CFDST) members We evaluate the seismic performance of stiffened CFDST members in terms of stiffness, strength, ductility, etc We propose a simplified model to predict the flexural strength of stiffened CFDST beam-columns.